Difficult catheter access to the occluded vessel during endovascular treatment of acute ischemic stroke is associated with worse clinical outcome. (31st October 2012) - Ribo, Marc; Flores, Alan; Rubiera, Marta; Pagola, Jorge; Mendonca, Nuno; Rodriguez-Luna, David; Piñeiro, Soco; Meler, Pilar; Alvarez-Sabin, Jose; Molina, Carlos A
Abstract : Background and aim: During endovascular procedures for acute ischemic stroke, catheter access to the occluded vessel may be technically difficult or impossible. The aim of this study was to access the impact of difficult catheter access to target the carotid artery on clinical outcome. Methods: Anterior circulation stroke patients undergoing transfemoral endovascular procedures where studied. Patients were divided into four groups according to time from groin puncture to target carotid catheterization quartiles. Patients in quartile 4 (Q4) were considered difficult carotid access. We defined several outcome measures: recanalisation (final Thrombolysis in Cerebral Infarction score ≥2a), time from groin puncture to recanalisation and favorable long term outcome (modified Rankin Scale score <3 at 3 months). Results: Of 130 patients studied, carotid catheterization was impossible in seven patients (5.1%). These patients had significantly lower rates of recanalization (14.3% vs 80.5%; p<0.01) and favorable outcome (0% vs 36%; p=0.038). Among patients with an accessible carotid artery(n=123), median time from groin puncture to carotid catheterization was 20 min (IQR 10). A negative correlation between time to carotid access and recanalization was observed (r=−0.31; p<0.01). Patients in Q4 (>30 min) had lower rates of recanalization (60.7% vs 82.4%; p=0.02) and a lower favorable outcome (13.6% vs 41.3%; p=0.04). A logistic regression adjusted by age showed that baseline National Institutes of Health Stroke Scale score (OR 0.8; 95% CI: 0.72 to 0.92 p<0.01) and having difficult access (OR 1.3; 95% CI 1.3 to 20.1 p=0.018) independently predicted worse long term outcome. Conclusions: Difficult catheter access to target the carotid is common during acute endovascular treatment of stroke patients and is associated with a worse clinical outcome. If transfemoral access appears difficult, alternative access such as direct carotid puncture could be explored.